Predicting intentions of nurses to adopt patient personal health records: A structural equation modeling approach. (November 2016) - Chung, Min-Huey; Ho, Cheng-Hsun; Wen, Hsyien-Chia
Highlights: Personal health records (PHRs) enhance multidisciplinary communication of providers. No previous evidence was found on predicting nurses' intentions to adopt patient PHRs. Few studies have used an extended technology acceptance model to explore medical information technology-related factors. Evidence of how subjective norms influence nurses' attitudes for patient PHRs is provided. Nurses had positive attitudes of using patient PHRs when it is encouraged by supervisors and colleagues. Abstract: Objective: The American Nurses Association endorsed the use of online patient personal health records (PHRs) and challenged all nurses to obtain the health records of patients. However, few studies have explored the factors associated with the intentions of nurses to use patient PHRs. Our study used an extended technology acceptance model, with the theory of planned behavior and perceived credibility, to explore factors associated with the intentions of nurses to use patient PHRs. Methods: This cross-sectional quantitative study comprised a sample of 635 nurses who had worked full time for at least 3 months, and they were recruited from three hospitals affiliated with a university in northern Taiwan. We used a questionnaire to obtain information on perceived usefulness, perceived ease of use, perceived credibility, subjective norms, computer self-efficacy, attitudes, and intentions to use patient PHRs. Results: This study indicated that perceived usefulness, computer self-efficacy, and subjective norms significantly and positively affected intentions to use patient PHRs. The attitudes of nurses toward PHR adoption directly influenced their intentions to use patient PHRs. Moreover, subjective norms indirectly affected intentions to use patient PHRs through the factor of attitudes. The proposed model explained 82.1% of the variance in the intentions of nurses to use patient PHRs. Conclusions: Subjective norms had stronger total effects on the attitudes and intentions of nurses to use patient PHRs than perceived usefulness, perceived ease of use, or perceived credibility did. The results may help practitioners further understand that the attitudes of nurses toward using patient PHRs are influenced by peer groups and administrators. The current study provides evidence that peer groups influence the attitudes of nurses to use patient PHRs, which in turn influence their intentions toward PHR adoption.